Soundings in Critical Theory - LaCapra, Dominick, 1939- (Book collections on Project MUSE., 1989)
"Dominick LaCapra is unequalled in his ability to bring theoretical concerns that are associated with literary theory to the attention of historians. He is responsible for enlivening the discipline of history and compelling historians to rethink their foundational assumptions, which normally go unquestioned."--Mark Poster, University of California, Irvine